Scheduling of home energy management systems for price-based demand response and end-users discomfort reduction - Kamyab Gholam-Reza (Serbian Journal of Electrical Engineering)
The home energy management system (HEMS) can effectively participate in price-based demand response programs, significantly reducing electricity costs by optimizing the usage times of shift-able household appliances such as washing machines, dishwashers, and others. However, this optimization may compromise the comfort of the residents. In this paper, a discomfort index is proposed based on the time intervals between the start and end of the operation periods of these shift-able appliances relative to their residents' preferred usage times. The problem of optimal scheduling for these appliances is then modeled as an optimization problem aimed at minimizing the weighted sum of the daily household electricity bill and the discomfort index. A constraint is imposed to restrict the discomfort index to a maximum allowable level. This optimization problem is solved using a simulated annealing algorithm across various scenarios with different maximum allowable values for the discomfort index. The simulation results indicate that, among the optimal schedules across the scenarios, the most cost-effective demand response schedule can be identified based on the marginal reductions in the daily household electricity bill. This approach ensures substantial decreases in electricity expenses while avoiding unnecessary increases in the discomfort index.